North Sumatra Regional Police Policy In Eradicated Human Trafficking Using Online Prostitution Mode - Aminudin Aminudin; Chaisyah Aliffah Siswoyo (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
Human trafficking is a punishable offense involving acts of violence, intimidation, or abhorrent behavior, kidnapping, imprisonment, forgery, and other crimes such as recruitment, transportation, harboring, and shipping. This study examines the policies implemented by the North Sumatra Regional Police in eradicating human trafficking through online prostitution. The importance of this research lies in the fact that human trafficking is a serious violation of humanity. The practice of human trafficking through online prostitution is increasingly rampant in Indonesia, especially in North Sumatra. Therefore, the role of all levels of society and state institutions in the legal field is needed to take decisive action to eradicate human trafficking through online prostitution. It is hoped that this article will encourage the police, especially in the North Sumatra region, to apply these findings to formulate measures against human trafficking through online prostitution, which is a crucial aspect of investigations.